Expression of the Self-Sharpening Mechanism of a Roller Cone Bit during Wear Due to the Influence of the Erosion Protection Carbide Coating - Jurij Šporin (MDPI AG, 2021)
Roller cone drill bits are used in drilling larger diameter wells. The drilling efficiency of the roller cone drill bit depends on the wear rate of the materials that forms bit teeth, which crushes the rock at the bottom of the well. To prevent excessive wear, research has largely focused on the study and determination of abrasion-resistant materials. In our work, we investigated the wear mechanism of a roller cone drill bit whose wear-resistant teeth are protected by a hard metal coating welded onto the teeth. The difference between material properties of erosion-protective carbide coating and the tooth steel leads to uneven wear of bit teeth. In order to determine the material changes, we carried out detailed studies of the rock through which drilling was carried out, the drilling parameters and the materials of which the roller cone bit is made. The principle of wear of the tooth materials and their carbide coating, determined by our research, indicated the guidelines which could be basis for the development of abrasion-resistant materials could be carried out, as well as the problem of applying an erosion protection to the teeth of the studied type of roller cone bits.